In Search of a Theory of Everything: What if the Universe was an elastic and massive lattice and we were its topological singularities? - Gremaud, Gérard (JOURNAL OF ADVANCES IN PHYSICS, 2020)
In this brief communication, we summarize an original and new approach of the Universe, which considers that the Universe could be a finite, elastic and massive solid that would move and deform in an infinite absolute vacuum. In this a priori strange concept, it is supposed that the Universe is a lattice of simple cubic crystalline structure, whose basic cells have a mass of inertia that satisfies Newtonian dynamics in absolute space, and whose elasticity is controlled by the existence of an internal energy of deformation. One also supposes that this lattice is likely to contain topological singularities, i.e. structural defects such as dislocations, disclinations and dispirations, which would be the constituent elements of Ordinary Matter.